Design of a W-band, 100 kW, frequency doubling gyroklystron amplifier - Chauhan M.S.; Yuvaraj S.; Jain P.K.; Kartikeyan M.V. (My University, 2025)
In this paper, a two-cavity W-band frequency doubling gyroklystron amplifier has been designed. The single mode nonlinear analysis for studying the beam-wave interaction behavior in a frequency doubling gyroklystron amplifier has been developed by combining the theory of harmonic operation of gyroklystron amplifier with the fundamental mode operation. Consequently, the RF output power, efficiency, and bandwidth of the gyroklystron amplifier has been computed. The results from the developed nonlinear analysis predicted a stable RF output power of 116 kW at 94 GHz, with 20.6 dB gain, 32.2% efficiency and a bandwidth of 0.32% for a 60 kV, 6 A gyrating electron beam. © 2018 IEEE.